2019
DOI: 10.1111/odi.13046
|View full text |Cite
|
Sign up to set email alerts
|

Systemic comorbidities are associated with medication‐related osteonecrosis of the jaws: Case–control study

Abstract: Objectives Medication‐related osteonecrosis of the jaws (MRONJ) is a serious condition developed in up to 15% of patients who take antiresorptive medications. Its underlying pathogenesis remains unclear. The association between systemic comorbidities and MRONJ was investigated. Subjects and Methods A case–control study was conducted in Brisbane, Australia. Hospital records were used to identify 68 cases of MRONJ between January 2003 and March 2017. Each case was individually matched to three controls (204 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Aside from cancer and osteoporosis, there are an increasing number of other conditions with case reports of MRONJ, such as rheumatoid arthritis (RA) 14,39,40 . Several implicated drugs in this study, including adalimumab, cyclophosphamide, etanercept, methotrexate and rituximab, have indications for RA as well as other auto‐immune conditions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Aside from cancer and osteoporosis, there are an increasing number of other conditions with case reports of MRONJ, such as rheumatoid arthritis (RA) 14,39,40 . Several implicated drugs in this study, including adalimumab, cyclophosphamide, etanercept, methotrexate and rituximab, have indications for RA as well as other auto‐immune conditions.…”
Section: Discussionmentioning
confidence: 96%
“…36,37 Aside from cancer and osteoporosis, there are an increasing number of other conditions with case reports of MRONJ, such as rheumatoid arthritis (RA). 14,39,40 Several implicated drugs in this study, including adalimumab, cyclophosphamide, etanercept, methotrexate and rituximab, have indications for RA as well as other auto-immune conditions. The disease process of RA is characterised by high levels of proinflammatory cytokines that leads to increased bone resorption, progressive joint destruction, osteoporosis and increased fracture risk.…”
Section: It Has Been Reported In the Aaoms Paper And The Internationalmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a study by McGowan et al found the incidence of MRONJ in patients on multiple medications with systemic comorbidities was higher. 10 Hence intensive dental preventative advice and careful planning and monitoring of these patients after starting medications that can cause MRONJ, must be at the forefront of care.…”
Section: Discussionmentioning
confidence: 99%